A narrative systematic review of life skills education: effectiveness, research gaps and priorities - Nasheeda, Aishath; Abdullah, Haslinda; Krauss, Steven Eric; Ahmed, Nobaya (Routledge, 2019)
A systematic review was conducted to investigate the literature on effectiveness of life skills programs. The aim of this review was to gain a comprehensive understanding on the effectiveness of life skills education globally, and to identify research gaps and priorities. Findings revealed differences in life skills education within developing countries and developed countries. In general, developed countries conduct more systematic life skills education programs promoting positive behavior, with research articulating outcomes on individual youth. In contrast, the majority of developing countries’ life skills programs lack systematic implementation, evaluation and monitoring. Programs are often conducted to yield short term results only. This review will be useful to administrators, policy makers, researchers and teachers to implement effective life skills programs. The findings can be used as inputs for developing sustainable life skills programs to ensure transfer of knowledge and skills.